Dysphagia in frail elderly: self-reported mealtime symptoms and risk - Cirley Novais Valente Junior; Fernanda Chiarion Sassi; Ana Paula Ritto; Isadora Cardoso Salles Fila Pecenin; Claudia Regina Furquim de Andrade (Revista de Saúde Pública)
ABSTRACT OBJECTIVE: This study aimed to characterize swallowing and investigate the association between self-reported coughing and/or choking during meals and the risk of dysphagia in frail elderly individuals receiving healthcare at a specialized center in São Paulo, Brazil. METHODS: This cross-sectional observational study included elderly individuals attending an Elderly Health Reference Unit (URSI) from July 2017 to December 2023. Data from all patients referred to the URSI were collected, excluding only those with incomplete medical records. The study proceeded in two phases: the first phase involved physical, functional, and social assessments, while the second phase included speech and swallowing evaluations. Participants were categorized into groups based on self-reported mealtime symptoms. Descriptive and inferential analyses compared these groups using the Mann-Whitney U test for quantitative data and Pearson's χ2 test for qualitative data. Risk analysis employed multiple logistic regression with forward stepwise selection. RESULTS: The study comprised 1,027 elderly individuals (mean age 78 years; 68.2% women; 64.2% self-identified as white). Approximately half reported frequent choking during meals. Sex, Multidimensional Assessment of the Elderly in Primary Care classification and score, polypharmacy, chronic diseases, falls, urinary incontinence, osteoporosis, cardiac disease, last dental visit, speech difficulty, change in food consistency, hearing loss, and hearing aid use were associated with mealtime symptoms. Speech alterations increased bronchoaspiration risk by 16%, memory complaints by 11%, and xerostomia and food consistency changes by 8%. CONCLUSION: Speech alterations, changes in food consistency, memory complaints, and xerostomia were identified as factors increasing the risk of bronchoaspiration. Early identification and a multidisciplinary approach to swallowing disorders in frail elderly individuals are crucial for preventing aspiration pneumonia and maintaining quality of life. These findings underscore the significance of proactive management strategies in clinical practice.